2002
DOI: 10.1093/jnci/94.2.108
|View full text |Cite
|
Sign up to set email alerts
|

Slower Metabolism and Reduced Intake of Nicotine From Cigarette Smoking in Chinese-Americans

Abstract: The lower nicotine (and, therefore, tobacco smoke) intake per cigarette and the fewer cigarettes smoked per day, which may result, in part, from slower clearance of nicotine, may explain lower lung cancer rates in Chinese-Americans. Lower lung cancer rates among Latinos compared with whites, given their similar nicotine intake per cigarette, are probably due to smoking fewer cigarettes. The results with Chinese-Americans may have implications for dosing with nicotine medications to aid smoking cessation in Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
146
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(155 citation statements)
references
References 30 publications
8
146
1
Order By: Relevance
“…Pharmacokinetic parameter means in MZ and DZ twins are comparable to those published in previous studies using the same methodology for computing metabolic parameters but different samples of women and men of European descent (Benowitz, Perez-Stable et al, 2002;Perez-Stable et al, 1998). Consistency across studies validates the measurement of nicotine metabolic phenotypes, which may represent more biologically relevant phenotypes to understanding tobacco use and nicotine dependence .…”
Section: Generalizability Of the Study Samplesupporting
confidence: 70%
See 1 more Smart Citation
“…Pharmacokinetic parameter means in MZ and DZ twins are comparable to those published in previous studies using the same methodology for computing metabolic parameters but different samples of women and men of European descent (Benowitz, Perez-Stable et al, 2002;Perez-Stable et al, 1998). Consistency across studies validates the measurement of nicotine metabolic phenotypes, which may represent more biologically relevant phenotypes to understanding tobacco use and nicotine dependence .…”
Section: Generalizability Of the Study Samplesupporting
confidence: 70%
“…This article describes the convergence of two lines of work that, until now, have evolved independently of each other: (a) biometric genetic studies in twins have demonstrated a significant role for genetic influences on tobacco use and nicotine dependence (Carmelli et al, 1992;Heath & Madden, 1995;Kendler et al, 1999;Lessov et al, 2004;Li et al, 2003;McGue et al, 2000;Swan & Carmelli, 1997;True et al, 1999) and (b) laboratory pharmacology studies have characterized nicotine metabolic pathways (Benowitz & Jacob, 1997; see Figure 1), documented individual stability over time in nicotine disposition and kinetics, and reported substantial between-subject variability on these parameters (Benowitz & Jacob, 1994;Benowitz, Perez-Stable et al, 2002;Perez-Stable et al, 1998).…”
Section: Figurementioning
confidence: 99%
“…There is some evidence that differences in nicotine metabolism may contribute to differences in the intensity of smoking between Caucasians and Orientals. Benowitz et al (2002) have reported slower clearance and reduced intake of nicotine from cigarette smoking among Chinese-Americans than whites, that they postulate may cause Asian smokers to smoke fewer cigarettes per day. This issue has not been resolved.…”
Section: Lung Cancer Risk In Asians Versus Caucasiansmentioning
confidence: 99%
“…99 Lung cancer rates are lower in Asians and Latinos than Whites. 100 Chinese Americans exhibit a lower nicotine intake per cigarette, smoke fewer cigarettes per day, and exhibit a slower clearance of nicotine. The implication is that Chinese Americans, and perhaps other Asians, may require lower doses of NRTs.…”
Section: Cultural and Ethnic Minoritiesmentioning
confidence: 99%
“…The implication is that Chinese Americans, and perhaps other Asians, may require lower doses of NRTs. 100 Latinos exhibit similar nicotine intake per cigarette to whites, but smoke fewer cigarettes.…”
Section: Cultural and Ethnic Minoritiesmentioning
confidence: 99%